2012
DOI: 10.1175/2011jcli4139.1
|View full text |Cite
|
Sign up to set email alerts
|

Dynamically Derived Tropical Cyclone Intensity Changes over the Western North Pacific

Abstract: The study of the impact of global warming on tropical cyclone (TC) intensity is subject to uncertainty in historical datasets, especially in the western North Pacific (WNP) basin, where conflicting results have been found with the TC datasets archived in different organizations. In this study the basinwide TC intensity in the WNP basin is derived dynamically with a TC intensity model, based on the track data from the Joint Typhoon Warning Center (JTWC), the Regional Specialized Meteorological Center (RSMC) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
68
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 71 publications
(75 citation statements)
references
References 26 publications
7
68
0
Order By: Relevance
“…The landfall rarity of intense North Indian Ocean hurricanes means the data are too noisy for analysis. For the western North Pacific the trend is very weak and slightly negative, which we attribute to a general eastward and equatorward movement of the main genesis location in recent decades (Wu and Zhao 2012). This promotes the development of a higher proportion of intense hurricanes, but also means that fewer of them will make landfall.…”
Section: Analysis Issuesmentioning
confidence: 75%
See 3 more Smart Citations
“…The landfall rarity of intense North Indian Ocean hurricanes means the data are too noisy for analysis. For the western North Pacific the trend is very weak and slightly negative, which we attribute to a general eastward and equatorward movement of the main genesis location in recent decades (Wu and Zhao 2012). This promotes the development of a higher proportion of intense hurricanes, but also means that fewer of them will make landfall.…”
Section: Analysis Issuesmentioning
confidence: 75%
“…The weaker trend may be attributed to two factors: the automated Dvorak analysis used by Kossin may underestimate the most intense storms, or there may be an artificial analysis trend in the archived data. On a regional basis, Wu and Zhao (2012) applied the Emanuel (2008) dynamical downscaling approach to reanalysis data for the western North Pacific and found a significant increase in the frequency of Cat 4-5 hurricanes ( Table 1) that is similar to that in Fig. 4b after taking proportions, but at around half the rate.…”
Section: Analysis Issuesmentioning
confidence: 93%
See 2 more Smart Citations
“…Recent studies (Wu and Zhao 2012; suggested that the frequency of intense TCs (categories 4 and 5 on the Saffir-Simpson scale) and the lifetime maximum intensity are more sensitive to large-scale environmental conditions and changes. Thereby, the two metrics are employed to investigate the inter-annual variability of TC intensity.…”
Section: Comparison Of Tc Simulations Using the Two Types Of Ensemblementioning
confidence: 99%